2001
DOI: 10.1007/s003840100287
|View full text |Cite
|
Sign up to set email alerts
|

Increased matrix metalloproteinase 2 concentration and transcript expression in advanced colorectal carcinomas

Abstract: Colorectal cancer is one of the most common malignant tumors and entails a relatively poor prognosis. Clinical outcome depends on the extent of local and metastatic tumor spread. Results of in vivo and in vitro studies suggest that the balance between matrix metalloproteinases (MMPs) and their inhibitors (tissue inhibitors of metalloproteinases TIMPs) is altered in neoplasia, contributing to the invasive and metastatic properties of malignant tumors. We quantified tissue concentrations of MMP-2 and TIMP-2 in 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 31 publications
2
18
0
2
Order By: Relevance
“…The observed increase in MMP-2 expression observed in tumor samples is consistent with previous studies of breast (41,42), colon (43)(44)(45)(46)(47), stomach (48,49), lung (50 -53), rectal (43,54), and kidney cancer (55)(56)(57). Whereas a strong association of increased MMP-3 has been found in breast cancer (41, 58 -61), the increased expression levels observed in other tumor types are not as well supported by published literature.…”
Section: Sibling Expression and Tumor Progressionsupporting
confidence: 91%
“…The observed increase in MMP-2 expression observed in tumor samples is consistent with previous studies of breast (41,42), colon (43)(44)(45)(46)(47), stomach (48,49), lung (50 -53), rectal (43,54), and kidney cancer (55)(56)(57). Whereas a strong association of increased MMP-3 has been found in breast cancer (41, 58 -61), the increased expression levels observed in other tumor types are not as well supported by published literature.…”
Section: Sibling Expression and Tumor Progressionsupporting
confidence: 91%
“…Similar to studies by Ring (16) and Papandopoulou (25), we found higher MMP-2 expression in high-grade tumors, although some studies show the opposite finding (13,19). Since tumor grade and vascular invasion are well-known prognostic factors (26), their correlation with MMP-2 positive immunostaining puts them in the group of pathohistological parameters characteristic for aggressive tumor behavior.…”
Section: Discussionsupporting
confidence: 77%
“…Previous studies on MMP-2 protein expression as a prognostic marker in colon carcinoma used various methods, including gelatin zymography (19), enzyme linked immunosorbent assays (19), quenched fluorescence substrate hydrolysis (20), Western blot (19), in situ hybridization (19), and immunohistochemistry on formalin fixed, paraffin embedded tissue (17,18). Immunohistochemistry has several advantages over other methods -it allows direct correlation with morphology and it can be performed on paraffin embedded specimens, which makes it practical for the routine assessment of MMPs in diagnostic practice.…”
Section: Discussionmentioning
confidence: 99%
“…Роль матриксных металлопротеиназ (ММП) в опухолевой прогрессии [2]. [13][14][15][16][17][18][19][20][21], а использование природных и синтетических ингибито-ров ММП считается перспективным подходом к противо-опухолевой терапии [2,13].…”
Section: актуальные вопросы онкологииunclassified